Plant performance was greater in the soils of more distantly related plants for an herbaceous understory species - Sweet, Drake D. (AoB Plants, 2017)
Growing evidence suggests that plant–soil interactions have important implications for plant community composition. However, the role of phylogenetic relatedness in governing interactions between plants and soil biota is unclear, and more case studies are needed to help build a general picture of whether and how phylogeny might influence plant–soil interactions. We performed a glasshouse experiment to test whether degree of phylogenetic relatedness between Aquilegia canadensis and six co-occurring heterospecifics affects A. canadensis biomass through soil legacy effects. We also compared performance of A. canadensis in soils conditioned by invasive Alliaria petiolata versus native heterospecifics, hypothesizing that conditioning by A. petiolata would suppress the performance of the focal native plant. A. canadensis performed significantly better in distant relatives’ soils than in close relatives’ soils, and this effect disappeared with soil sterilization, consistent with close relatives sharing similar pathogens. Contrary to our expectations, soils conditioned by the invasive species A. petiolata versus by native species had similar effects on A. canadensis. The greater performance of A. canadensis in soils of more versus less distant relatives is consistent with a hypothesis of phylogenetically constrained pathogen escape, a phenomenon expected to promote coexistence of phylogenetically distant species. However, pairwise plant–soil feedback experiments are needed to create a stronger coexistence prediction.